Analisis Proses Pengendalian Mutu dalam Pelaksanaan Standar Pelayanan Minimal (SPM) di Instalasi Farmasi RS Keluarga Sehat - LIa Alfa Rosida; Sudiro Sudiro (Jurnal Manajemen Kesehatan Indonesia, 2017)
The indicator achievement of minimum service standard (MSS) for the accuracy of distributingdrugs in Pharmacy Unit of Keluarga Sehat Hospital has not been achieved, even the incidence ofthe distributionerror from 2013 to 2016 continues to increase. The purpose of this researchwas to analyze the quality control process in the implementation of MSS in Pharmacy Unit of Keluarga Sehat Hospital. This was a qualitative research, with research subject 3pharmacy officers and 3 people of pharmacy management services.Data collectedby in-depth interview and observation of pharmaceutical performance report data and analysed by content analysis. The result of the research showed that the evaluation of pharmacy staff performance has not been implemented, because there is no performance appraisal indicator yet. Comparison was done only by comparing reports with general target, medical support manager double job resulted in no feedback to Pharmacy Unit, and so it has not supported the implementation of MSS. The Improvement of performancehas not been implementedand has notfound the concept of improvement. The new management will attempt to conduct a comparative study, including pharmacy installation into the Quality Control Group (GKM) or Problem Solving for Better Health (PSBH), find the cause of the problem and develop the policy. It can be concluded that the quality control of the MSS in the Pharmacy Unit still not going well and need to be improved especially related to quality performance appraisal and performance improvement based on the SOP.